Cardiac CT Imaging Diagnosis of Cardiovascular Disease - Budoff, Matthew J.; Shinbane, Jerold S.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2010)
The comprehensive assessment of cardiovascular structure and function with computed tomography (CT) has progressed at an astounding rate due to advances in scanning technology and image processing. Given the growing importance of cardiovascular CT, this book collates all relevant imaging findings and presents them in a clinically relevant and practical manner appropriate for the spectrum of physicians who diagnose and treat cardiovascular disease. The chapters have been written by an internationally renowned group of contributing authors and present discussion and images which characterize the full spectrum of cardiovascular CT.
Overview -- Computed Tomography: Overview -- Cardiovascular Computed Tomography: Current and Future Scanning System Design -- Radiation Safety: Radiation Dosimetry and CT Dose Reduction Techniques -- Coronary Artery Calcium -- Assessment of Cardiovascular Calcium: Interpretation, Prognostic Value, and Relationship to Lipids and Other Cardiovascular Risk Factors -- Natural History and Impact of Interventions on Coronary Calcium -- The Aorta and Great Vessels -- CT Coronary Angiography -- Methodology for CCTA Image Acquisition -- Postprocessing and Reconstruction Techniques for the Coronary Arteries -- Coronary CT Angiography: Native Vessels -- Coronary Angiography After Revascularization -- CT Angiography Assessment for Cardiac Pathology -- Assessment of Cardiac Structure and Function by Computed Tomography Angiography -- Perfusion and Delayed Enhancement Imaging -- Pericardial/Myocardial Disease Processes -- Computed Tomography Evaluation in Valvular Heart Disease -- Assessment of Cardiac and Thoracic Masses -- CT Vascular Angiography -- CT Angiography of the Peripheral Arteries -- Aortic, Renal, and Carotid CT Angiography -- Assessment of Pulmonary Vascular Disease -- Multidisciplinary Topics -- Comparative Use of Radionuclide Stress Testing, Coronary Artery Calcium Scanning, and Noninvasive Coronary Angiography for Diagnostic and Prognostic Cardiac Assessment -- Cardiovascular Magnetic Resonance Imaging: Overview of Clinical Applications -- Computed Tomographic Angiography in the Assessment of Congenital Heart Disease -- CT Imaging: Cardiac Electrophysiology Applications -- An Interventionalist$1 (Bs Perspective: Diagnosis of Cardiovascular Disease -- CCTA: Cardiothoracic Surgery Applications -- Orientation and Approach to Cardiovascular Images.s
Keywords: Medicine; Radiology, Medical; Internal medicine; Cardiology; Heart -- Surgery; Medicine & Public Health; Cardiology; Imaging / Radiology; Diagnostic Radiology; Internal Medicine; Cardiac Surgery